Volatility Transmission among G-8 Countries - Bhuyan, Rafiqul (2013)
This paper investigates the volatility transmission in the financial markets of G-8 countries by using the VAREGARCH techniques. From the empirical analyses, it shows that volatility transmissions are present between the G-8 countries during the period from 1995 to 2007. The analyses indicate that the volatilities of some of the G-8 countries are due to the volatility from other markets. Of the countries whose volatilities are significantly affected by the volatility of other markets are: Canada, France, Italy, the UK and the USA. Among these five countries, Canada, the UK and the USA seem to be very highly inter-related. The countries that are very dominant in terms of transmitting volatility are: Russia and the USA. Interestingly, Japanese markets do not seem to have any significant effect on other G-8 markets. However, there have been significant volatility transmissions from the financial markets of Canada, Russia and the UK to the Japan markets. The paper contributes to the literature by studying the volatility transmission among the G-8 countries using the daily stock market data. It shows that the volatility transmission among the developed markets exist and seem to persist over time.